Ionic liquid-based electrolyte, wide-temperature-range high-voltage supercapacitor and application of wide-temperature-range high-voltage supercapacitor

By using a wide temperature domain ionic liquid-based electrolyte and rolling method in supercapacitors to prepare thin-film electrodes, the problem of insufficient energy density and working temperature zone of the existing supercapacitors is solved, and the advantages of high energy density, high power density and wide temperature zone operation are achieved.

CN119650315APending Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311203402.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing supercapacitors have shortcomings in energy density and working temperature zones, especially commercial activated carbon as an active substance, which has problems with low energy density and narrow working temperature zones.

Method used

A wide temperature domain ionic liquid-based electrolyte is used to design a high electrochemical window, low melting point, high boiling point, low viscosity, and high conductivity electrolyte through the combination of a eutectic ionic liquid system and an organic solvent, and a thin film-type electrode is prepared in combination with the rolling method.

Benefits of technology

It realizes the high energy density and high power density of supercapacitors in a wide temperature range, and the electrodes have high loading properties, which are suitable for industrial production, and have simple structural design, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650315A_ABST
    Figure CN119650315A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic liquid-based electrolyte, a wide-temperature-range high-voltage supercapacitor and application of the wide-temperature-range high-voltage supercapacitor. The wide-temperature-range high-voltage supercapacitor comprises a eutectic ionic liquid system and an organic solvent, the eutectic ionic liquid system comprises at least two ionic liquids; the ionic liquid comprises cations and anions; the positive ions are selected from at least one of pyrrolidinyl positive ions, piperidinyl positive ions, imidazolyl positive ions and quaternary ammonium positive ions containing different side chains; the anion is selected from at least one of tetrafluoroborate, hexafluorophosphate, bis (trifluoromethylsulfonyl imine), bis (fluorosulfonyl imine) and tetracyanoborate; the organic solvent comprises at least one of fluorinated carbonic ester, fluorinated carboxylic ester, sulfones, ethers and nitriles. The supercapacitor based on the ionic liquid-based electrolyte can stably operate in a wide temperature range, so that the wide-temperature-range high-voltage supercapacitor can be suitable for an extreme working environment, and high energy density and power density are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an ionic liquid-based electrolyte, a wide temperature range high-voltage supercapacitor and applications thereof, and belongs to the technical field of energy storage devices. Background Art

[0002] With the shortage of primary energy and the intensification of the greenhouse effect, the use of renewable energy is particularly important. Energy storage, as one of the most basic links in the use of renewable energy, can be subdivided into electrochemical energy storage, physical energy storage, electromagnetic energy storage, etc. Electrochemical energy storage can currently be subdivided into methods such as the Faraday reaction as the energy storage principle and the physical adsorption and desorption as the energy storage principle. The typical representative of the Faraday reaction as the energy storage principle is the lithium-ion battery, which has the advantages of high energy density, but the disadvantages are low power density, short life, and poor safety. The typical representative of the physical adsorption and desorption as the energy storage principle is the supercapacitor, which has the advantages of high power density and long life, but the disadvantages are low energy density and severe self-discharge.

[0003] One of the differences between double-layer supercapacitors and traditional capacitors is that they are composed of two high-surface electrode materials connected in series, with an electronically insulating ion-conducting electrolyte in the middle. Its electrolyte can be further divided into aqueous electrolyte, organic electrolyte, and ionic liquid-based electrolyte. Compared with the first two, the advantages of ionic liquid-based electrolytes are wide voltage window, high temperature resistance, non-volatility, and non-toxicity, and its disadvantages are high viscosity and low conductivity. Ionic liquids can be divided into imidazole type, pyridine type, piperidine type, quaternary ammonium type, quaternary phosphonium type, etc. according to cations, and their anions can be further divided into tetrafluoroborate, hexafluorophosphate, bis(trifluoromethylsulfonyl imide), bisfluorosulfonyl imide, dicyandiamide, etc.

[0004] Currently, commercial activated carbon is widely used in the market as an active material for supercapacitors, but it still has problems such as low energy density and narrow operating temperature range. One way to improve its energy density and operating temperature range is to use ionic liquid-based electrolytes, because ionic liquids are resistant to high pressure and high temperature, and through reasonable design, they can achieve low melting point, high boiling point, low viscosity, and high conductivity. Summary of the invention

[0005] According to one aspect of the present application, an ionic liquid-based electrolyte is provided that can operate stably in a wide temperature range.

[0006] This application adopts the following technical solutions:

[0007] An ionic liquid-based electrolyte comprises a eutectic ionic liquid system and an organic solvent;

[0008] The eutectic ionic liquid system comprises at least two ionic liquids;

[0009] The ionic liquid includes cations and anions;

[0010] The cation is selected from at least one of a pyrrolidinyl cation, a piperidinyl cation, an imidazolyl cation, and a quaternary ammonium cation having different side chains;

[0011] The anion is selected from at least one of tetrafluoroborate, hexafluorophosphate, bis(trifluoromethylsulfonyl imide), bis(fluorosulfonyl imide) and tetracyanoborate;

[0012] The organic solvent comprises at least one of fluorinated carbonates, fluorinated carboxylates, sulfones, ethers, and nitriles.

[0013] The boiling point of the organic solvent is higher than room temperature;

[0014] Optionally, the nitrile is selected from at least one of glutaronitrile, acetonitrile, butyronitrile, adiponitrile and propionitrile.

[0015] Optionally, the electrochemical window of the ionic liquid at -20 to 85° C. is greater than 2.5 V;

[0016] The melting point of the ionic liquid is less than 30°C;

[0017] The boiling point of the ionic liquid is greater than 300°C.

[0018] In the eutectic ionic liquid system, in at least two ionic liquids, when the cations are different, the anions may be the same or different; when the cations are the same, the anions are different.

[0019] Optionally, in the ionic liquid-based electrolyte, the weight ratio of the ionic liquid to the organic solvent is 1 to 9:1.

[0020] Optionally, in the ionic liquid-based electrolyte, the weight ratio of the ionic liquid to the organic solvent is selected from any value of 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or any range therebetween.

[0021] Optionally, the molar content of each ionic liquid in the eutectic ionic liquid system is 10 to 90%.

[0022] The above-mentioned ionic liquid-based electrolyte adopts the general design method of ionic liquid-based electrolytes that are resistant to high voltage and wide temperature range. The cations and anions are screened based on the density functional theory calculation of their corresponding anion and cation electrochemical windows, and then the anions and cations are combined, and a eutectic system of two or more ionic liquids is designed.

[0023] The selection of the above organic solvent is based on the theoretical calculation of the highest occupied orbital and the lowest unoccupied orbital to screen for organic solvents with high electrochemical stability and high boiling point. Among them, the screening principle is that the lower the energy level of the highest occupied orbital of the organic solvent, the better, and the higher the energy level of the lowest unoccupied orbital, the better.

[0024] According to another aspect of the present application, a supercapacitor is provided, which is a high working voltage double-layer ionic liquid-based supercapacitor, which is safe and controllable, environmentally friendly, low-cost, high-efficiency, and can achieve the advantages of high energy density, high power density and wide temperature range operation of the supercapacitor.

[0025] A supercapacitor comprising a thin film electrode and at least one of the above-mentioned ionic liquid-based electrolytes;

[0026] The thin film electrode is prepared by a roller pressing method.

[0027] Optionally, the supercapacitor is a button-type supercapacitor, comprising a positive electrode shell, a positive electrode collector, a positive electrode sheet, a separator, a negative electrode sheet, a negative electrode collector, and a negative electrode shell stacked in sequence from bottom to top;

[0028] The positive electrode sheet, the negative electrode sheet, and the separator are fully infiltrated with the ionic liquid-based electrolyte;

[0029] The positive electrode sheet and the negative electrode sheet are independently selected from thin film electrodes.

[0030] Optionally, the steps of preparing the thin film electrode by roller pressing method include:

[0031] The mixture containing active material, binder and conductive agent is mixed with solvent, stirred and ultrasonicated to obtain dispersion liquid, and then the dispersion liquid is dried to be viscous, rolled into a film and dried to obtain the film-type electrode.

[0032] Optionally, the drying method is selected from at least one of natural drying, normal pressure heating drying, vacuum drying, spray drying or freeze drying.

[0033] Optionally, the ultrasonic dispersion time is 0.1 to 2 hours.

[0034] Optionally, the active substance is selected from at least one activated carbon selected from YP50F, YPS, YP80F, and RP-20.

[0035] Optionally, the conductive agent is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and conductive graphite.

[0036] Optionally, the binder is selected from at least one of 60%wt polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate.

[0037] Optionally, the content of the active substance in the mixture is 70 to 95 wt %.

[0038] Optionally, the content of the binder in the mixture is 1 to 10 wt %.

[0039] Optionally, the content of the conductive agent in the mixture is 1 to 10 wt %.

[0040] Optionally, the weight ratio of the mixture to the solvent is 1:120-300.

[0041] Optionally, the solvent is selected from at least one of acetone, ethanol and N-methylpyrrolidone.

[0042] Optionally, the thickness of the positive electrode sheet and the negative electrode sheet is independently 0.4 to 0.6 mm.

[0043] The surface loading of the positive electrode sheet and the negative electrode sheet is independently 10 to 20 mg / cm 2 .

[0044] The weight ratio of the positive electrode composed of the positive current collector and the positive electrode sheet to the negative electrode composed of the negative current collector and the negative electrode sheet is 1:0.5-2.

[0045] Optionally, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of carbon-coated aluminum foil, aluminum foil, and titanium foil.

[0046] Optionally, the diaphragm is selected from at least one of a PP diaphragm, a cellulose diaphragm, a glass fiber diaphragm, and a PE diaphragm.

[0047] Optionally, the specifications of the negative electrode shell and the positive electrode shell are both CR2016.

[0048] Optionally, the operating voltage of the supercapacitor is 2 to 3V, and the operating temperature range is -30 to 85°C.

[0049] According to another aspect of the present application, there is also provided an application of the above-mentioned supercapacitor as an energy storage device.

[0050] The beneficial effects of this application include:

[0051] The wide temperature range high voltage supercapacitor provided by this application uses the design principles and screening methods of ionic liquid-based electrolytes to provide a variety of electrolytes with different requirements, so that the wide temperature range high voltage supercapacitor can be used in extreme working environments, achieve high energy density and power density, and use a thin film electrode made by a roller pressing method, which can achieve high electrode load, which is conducive to scale-up industrial production, and the production process technology route required for the structural design of the wide temperature range high voltage supercapacitor of this application is simple, which can realize industrial safety and large-scale production. In addition, the design principles and screening methods of the ionic liquid-based electrolyte of this application can also be extended to organic and aqueous electrolytes to provide a new design concept for them. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1This is a diagram of the electrode film prepared in Example 1 of the present application.

[0053] Figure 2 This is the DSC graph of the eutectic ionic liquid system in Example 1 of the present application.

[0054] Figure 3 This is the TG diagram of the eutectic ionic liquid system in Example 1 of the present application.

[0055] Figure 4 This is a graph of the capacity retention rate of the supercapacitor prepared in Example 1 of the present application.

[0056] Figure 5 These are SEM images of the supercapacitor prepared in Example 1 of the present application before (a) and after (b) constant current charge and discharge cycles. DETAILED DESCRIPTION

[0057] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0058] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0059] The analysis method in the examples of this application is as follows:

[0060] SEM analysis was performed using a Quanta-200F scanning electron microscope.

[0061] The capacity retention rate of button-type supercapacitors was tested using a LANHE battery tester.

[0062] Differential scanning calorimetry measurements were performed using Discovery DSC.

[0063] Thermogravimetric tests were performed using TG 209F1 LIBsra (NETZSCH).

[0064] Example 1

[0065] Weigh 1.6YP80F, 0.1g conductive graphite, and 0.1g PTFE, dissolve them in 200ml ethanol, stir for 10min, and ultrasonicate for 10min to obtain a uniform dispersion; dry the dispersion in a forced air drying oven at 100°C until it becomes viscous; use a roller press to roll the electrode precursor into a uniform and smooth film, and vacuum dry it in a vacuum oven at 100°C for 12h; use a 12mm diameter slicer to slice the electrode to obtain the electrode, and the slice is recorded as the electrode sample 1. After testing, the electrode film slice of the electrode sample 1 is as shown in the figure Figure 1 As shown, the obtained sample is uniform and has a smooth surface.

[0066] The ionic liquid-based electrolyte was prepared in a glove box, pyrrolidine and piperidine were selected as the cations in the eutectic ionic liquid, bis(fluorosulfonyl)imide was selected as the anion, and glutaronitrile was added as the organic solvent. The mass ratio of the three was 45:45:10. After testing, the DSC and TG graphs of the eutectic ionic liquid system 1 are as follows Figure 2 and Figure 3 As shown, from its DSC curve, it can be seen that the melting point of the electrolyte is lower than minus 100°C, and from its TG curve, it can be seen that the boiling point of the electrolyte is greater than 300°C.

[0067] The button-type supercapacitor is assembled in a glove box, and the electrode plates obtained above are used as positive electrode plates and negative electrode plates. The specific steps are as follows: assemble from bottom to top,

[0068] They are CR2016 positive electrode shell, 12mm diameter carbon-coated aluminum foil current collector, 12mm diameter positive electrode piece, 19mm diameter PP diaphragm, 12mm diameter negative electrode piece, 12mm carbon-coated aluminum foil current collector, and CR2016 negative electrode shell. Ionic liquid-based electrolyte is used to infiltrate the diaphragm and electrode piece in the middle. The amount of electrolyte added is 150μL. It is then packaged using a tablet press and recorded as supercapacitor 1.

[0069] After testing, the constant current charge and discharge cycle capacity retention rate of sample supercapacitor 1 is shown in the figure below: Figure 4 As shown in the figure, the capacitor can stably cycle for more than 10,000 cycles at a voltage of 3V at a temperature of 85°C. The SEM images of the electrode plate of sample supercapacitor 1 before and after constant current charge and discharge cycles are shown in the figure. Figure 5 As shown, the structure of the electrode did not change significantly before and after the cycle, indicating that the electrode structure has good stability.

[0070] Example 2

[0071] Weigh 2g YP50F, 0.1g conductive carbon black and 0.1g PVDF, dissolve them in 200ml N-methylpyrrolidone, stir for 60min, and ultrasonicate for 30min to obtain a uniform dispersion; bake the dispersion in a forced air drying oven at 120°C until it becomes viscous; use a roller press to roll the electrode precursor into a uniform and smooth film, and vacuum dry it in a vacuum oven at 120°C for 12h; use a 12mm diameter slicer to slice it to obtain an electrode plate, and the slice surface is similar to that of the plate sample 1.

[0072] The ionic liquid-based electrolyte was prepared in a glove box, pyrrolidine and piperidine were selected as cations in the eutectic ionic liquid, bis(fluorosulfonyl)imide was selected as anion, and acetonitrile was added as an organic solvent. The mass ratio of the three was 40:40:20. The DSC and TG test results of the obtained ionic liquid-based electrolyte were similar to those of ionic liquid system 1.

[0073] The button-type supercapacitor is assembled in a glove box, and the electrode plates obtained above are used as positive electrode plates and negative electrode plates. The specific steps are as follows: assemble from bottom to top,

[0074] The order is CR2016 positive electrode shell, 12mm diameter aluminum foil current collector, 12mm diameter positive electrode plate, 19mm diameter GF diaphragm, 12mm diameter negative electrode plate, 12mm diameter aluminum foil current collector, CR2016 negative electrode shell, ionic liquid-based electrolyte is used to infiltrate the diaphragm and electrode plate in the middle, the amount of electrolyte added is 50 microliters, and then it is packaged with a tablet press. The constant current charge and discharge cycle capacity retention rate of the obtained sample supercapacitor and the surface microstructure of the electrode plate before and after the constant current charge and discharge cycle are similar to those of sample supercapacitor 1.

[0075] Example 3

[0076] Weigh 3g YP80F, 0.15g carbon nanotubes, and 0.15g PTFE, dissolve in 300ml acetone, disperse, stir for 120min, and ultrasonicate for 60min to obtain a uniform dispersion; bake the dispersion in a forced air drying oven at 120°C until it becomes viscous; use a roller press to roll the electrode precursor into a uniform and smooth film, and vacuum dry it in a vacuum oven at 120°C for 4h; use a 12mm diameter slicer to slice to obtain an electrode pole piece, and the slice surface is similar to that of pole piece sample 1.

[0077] The ionic liquid-based electrolyte was prepared in a glove box, pyrrolidine and piperidine were selected as cations in the eutectic ionic liquid, bis(fluorosulfonyl)imide was used as anion, and butyronitrile was added as an organic solvent. The mass ratio of the three was 30:30:40. The DSC and TG test results of the obtained ionic liquid-based electrolyte were similar to those of ionic liquid system 1.

[0078] The button-type supercapacitor is assembled in a glove box, and the electrode plates obtained above are used as positive electrode plates and negative electrode plates. The specific steps are as follows: assemble from bottom to top,

[0079] The order is CR2016 positive electrode shell, 12mm diameter titanium foil current collector, 12mm diameter positive electrode sheet, 19mm diameter PP diaphragm, 12mm diameter negative electrode sheet, 12mm diameter titanium foil current collector, CR2016 negative electrode shell, ionic liquid-based electrolyte is used to infiltrate the diaphragm and electrode sheet in the middle, the amount of electrolyte added is 100μL, and then it is packaged with a tablet press. The constant current charge and discharge cycle capacity retention rate of the obtained sample supercapacitor and the surface microstructure of the electrode sheet before and after the constant current charge and discharge cycle are similar to those of sample supercapacitor 1.

[0080] Example 4

[0081] Weigh 0.5g YPS, 0.1g graphene and 0.1g PVDF, dissolve them in 200ml acetone, stir for 20min, and ultrasonicate for 30min to obtain a uniform dispersion; bake the dispersion in a forced air drying oven at 80°C until it becomes viscous; use a roller press to roll the electrode precursor into a uniform and smooth film, and vacuum dry it in a vacuum oven at 80°C for 6h; use a 12mm diameter slicer to slice it to obtain an electrode pole piece, and the slice surface is similar to that of pole piece sample 1.

[0082] The ionic liquid-based electrolyte was prepared in a glove box, pyrrolidine and piperidine were selected as cations in the eutectic ionic liquid, bis(fluorosulfonyl)imide was used as anion, and adiponitrile was added as an organic solvent. The mass ratio of the three was 30:40:30. The DSC and TG test results of the obtained ionic liquid-based electrolyte were similar to those of ionic liquid system 1.

[0083] The button-type supercapacitor is assembled in a glove box, and the electrode plates obtained above are used as positive electrode plates and negative electrode plates. The specific steps are as follows: assemble from bottom to top,

[0084] The order is CR2016 positive electrode shell, 12mm diameter carbon-coated aluminum foil current collector, 12mm diameter positive electrode sheet, 19mm diameter GF diaphragm, 12mm diameter negative electrode sheet, 12mm diameter carbon-coated aluminum foil current collector, CR2016 negative electrode shell, ionic liquid-based electrolyte is used to infiltrate the diaphragm and electrode sheet in the middle, the amount of electrolyte added is 150μL, and then it is packaged with a tablet press. The constant current charge and discharge cycle capacity retention rate of the obtained sample supercapacitor and the surface microstructure of the electrode sheet before and after the constant current charge and discharge cycle are similar to those of sample supercapacitor 1.

[0085] Example 5

[0086] Weigh 0.8g RP-20, 0.1g conductive graphite and 0.1g PVDF, dissolve in 40ml N-methylpyrrolidone, stir for 40min, and ultrasonicate for 30min to obtain a uniform dispersion; bake the dispersion in a forced air drying oven at 80°C until it becomes viscous; use a roller press to roll the electrode precursor into a uniform and smooth film, and vacuum dry it in a vacuum oven at 120°C for 6h; use a 12mm diameter slicer to slice to obtain an electrode plate, and the slice surface is similar to that of the plate sample 1.

[0087] The ionic liquid-based electrolyte was prepared in a glove box, pyrrolidine and piperidine were selected as cations in the eutectic ionic liquid, bis(fluorosulfonyl)imide was used as anion, and propionitrile was added as an organic solvent. The mass ratio of the three was 60:30:10. The DSC and TG test results of the obtained ionic liquid-based electrolyte were similar to those of ionic liquid system 1.

[0088] The button-type supercapacitor is assembled in a glove box, and the electrode plates obtained above are used as positive electrode plates and negative electrode plates. The specific steps are as follows: assemble from bottom to top,

[0089] The order is CR2016 positive electrode shell, 12mm diameter titanium foil current collector, 12mm diameter positive electrode sheet, 19mm diameter PP diaphragm, 12mm diameter negative electrode sheet, 12mm diameter titanium foil current collector, CR2016 negative electrode shell, ionic liquid-based electrolyte is used to infiltrate the diaphragm and electrode sheet in the middle, the amount of electrolyte added is 50μL, and then it is packaged with a tablet press. The constant current charge and discharge cycle capacity retention rate of the obtained sample supercapacitor and the surface microstructure of the electrode sheet before and after the constant current charge and discharge cycle are similar to those of sample supercapacitor 1.

[0090] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An ionic liquid-based electrolyte, characterized in that: Including eutectic ionic liquid system, organic solvent; The eutectic ionic liquid system comprises at least two ionic liquids; The ionic liquid includes cations and anions; The cation is selected from at least one of a pyrrolidinyl cation, a piperidinyl cation, an imidazolyl cation, and a quaternary ammonium cation having different side chains; The anion is selected from at least one of tetrafluoroborate, hexafluorophosphate, bis(trifluoromethylsulfonyl imide), bis(fluorosulfonyl imide) and tetracyanoborate; The organic solvent comprises at least one of fluorinated carbonates, fluorinated carboxylates, sulfones, ethers, and nitriles.

2. The ionic liquid-based electrolyte according to claim 1, characterized in that The electrochemical window of the ionic liquid at -20 to 85°C is greater than 2.5V; The melting point of the ionic liquid is less than 30°C; The boiling point of the ionic liquid is greater than 300°C.

3. The ionic liquid-based electrolyte according to claim 1, characterized in that In the ionic liquid-based electrolyte, the weight ratio of the ionic liquid to the organic solvent is 1 to 9:1; Preferably, the molar content of each ionic liquid in the eutectic ionic liquid system is 10-90%.

4. A supercapacitor, characterized in that: comprising at least one of a thin film electrode and an ionic liquid-based electrolyte according to any one of claims 1 to 3; The thin film electrode is prepared by a roller pressing method.

5. The supercapacitor according to claim 4, characterized in that: The supercapacitor is a button-type supercapacitor, comprising a positive electrode shell, a positive electrode current collector, a positive electrode sheet, a separator, a negative electrode sheet, a negative electrode current collector, and a negative electrode shell stacked in sequence from bottom to top; The positive electrode sheet, the negative electrode sheet, and the separator are fully infiltrated with the ionic liquid-based electrolyte; The positive electrode sheet and the negative electrode sheet are independently selected from thin film electrodes.

6. The supercapacitor according to claim 4, characterized in that: The steps of preparing thin film electrodes by roller pressing include: The mixture containing active material, binder and conductive agent is mixed with solvent, stirred and ultrasonicated to obtain dispersion liquid, and then the dispersion liquid is dried to be viscous, rolled into a film and dried to obtain the film-type electrode.

7. The supercapacitor according to claim 6, characterized in that: The active substance is selected from at least one activated carbon selected from YP50F, YPS, YP80F, and RP-20; Preferably, the conductive agent is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and conductive graphite; Preferably, the binder is selected from at least one of 60%wt polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate; Preferably, the content of the active substance in the mixture is 70 to 95 wt %; Preferably, the content of the binder in the mixture is 1 to 10 wt %; Preferably, the content of the conductive agent in the mixture is 1 to 10 wt %; Preferably, the weight ratio of the mixture to the solvent is 1:120-300; Preferably, the solvent is selected from at least one of acetone, ethanol and N-methylpyrrolidone.

8. The supercapacitor according to claim 5, characterized in that: The thickness of the positive electrode sheet and the negative electrode sheet are independently 0.4 to 0.6 mm; The surface loading of the positive electrode sheet and the negative electrode sheet is independently 10 to 20 mg / cm 2 ; The weight ratio of the positive electrode composed of the positive current collector and the positive electrode sheet to the negative electrode composed of the negative current collector and the negative electrode sheet is 1:0.5-2; Preferably, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of carbon-coated aluminum foil, aluminum foil, and titanium foil; Preferably, the diaphragm is selected from at least one of a PP diaphragm, a cellulose diaphragm, a glass fiber diaphragm, and a PE diaphragm.

9. The supercapacitor according to claim 5, characterized in that: The working voltage of the supercapacitor is 2 to 3V, and the working temperature range is -30 to 85°C.

10. Use of the supercapacitor according to any one of claims 4 to 9 as an energy storage device.

Citation Information

Patent Citations

  • Functionalized ionic liquid electrolyte for lithium secondary battery

    CN103035945A

  • Super capacitor high-voltage electrolyte and preparation method thereof

    CN103474255A

  • Abuse capacitor with wide temperature range and manufacturing method of abuse capacitor

    CN105304350A

  • Supercapacitor electrolyte and supercapacitor prepared by supercapacitor electrolyte

    CN107481870A

  • Additive for low-temperature electrolyte and application of ionic liquid as additive for low-temperature electrolyte

    CN108199082A

Cited By

  • Super capacitor ionic liquid mixed electrolyte with wide potential window and preparation method thereof

    CN120164730A

  • Wide potential window supercapacitor ionic liquid hybrid electrolyte and preparation method thereof

    CN120164730B